An HPLC‐UV method for determining plasma dimethylacetamide concentrations in patients receiving intravenous busulfan. (21st December 2016) - Cendana, Mildred; Lee, Samiuela; Upadhyay, Parth J.; Byrne, Jennifer A.; Shaw, Peter J.; Earl, John; Nath, Christa E.
Abstract: Dimethylacetamide (DMA) is a solvent used in the preparation of intravenous busulfan, an alkylating agent used in blood or marrow transplantation. DMA may contribute to hepatic toxicity, so it is important to monitor its clearance. The aim of this study was to develop an HPLC‐UV assay for measurement of DMA in human plasma. After precipitation of plasma proteins with acetonitrile followed by dilution (1:4) with water, the extract was injected onto the HPLC and detected at 195 nm. Separation was performed using a Cogent‐HPS 5 μm C18 column (250 × 4.6 mm) preceded by a Brownlee 7 μm RP18, pre‐column (1.5 cm × 3.2 mm). The mobile phase was 25 mm sodium phosphate buffer (pH 3), containing 2.5% ( v /v) acetonitrile and 0.0005% ( v /v) sodium‐octyl‐sulfonate. Using a flow rate of 1 mL/min, the retention times of DMA and the internal standard (IS), 2‐chloroacetamide, were 9.5 and 3.5 min, respectively. Peak area ratio (DMA:IS) was a linear function of concentration from 1 to 1000 μg/mL. There was excellent intraday precision (<5% for 5–700 μg/mL DMA), accuracy (<3% deviation from the true concentration) and recovery (74–98%). The limits of detection and quantification were 1 and 5 μg/mL, respectively. In eight children who received intravenous busulfan, DMA concentrations ranged from 110 to 438 μg/mL.